Peran Sentra Persiapan dalam Mengembangkan Motorik Halus Anak Usia 4–5 Tahun di TK Alam Yaa Bunayya Gresik - Indah Prasetyaningtyas; Rr. Agustien Lilawati; Fitri Ayu Fatmawati (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2026)
This study aims to describe learning activities in the preparation center and analyze their role in developing fine motor skills in children aged 4–5 years at TK Alam Yaa Bunayya Gresik. This research used a descriptive qualitative approach involving three children with fine motor development difficulties. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that tracing, cutting, coloring, pasting, and beading activities effectively stimulate eye–hand coordination, finger muscle strength, concentration, and independence. Differences in developmental outcomes were observed among participants, where children with better grip control and focus showed more optimal development. Thus, structured and repetitive learning activities in the preparation center play an important role in optimizing fine motor development in early childhood, especially for children with developmental delays.